An optimized probucol microencapsulated formulation integrating a secondary bile acid (deoxycholic acid) as a permeation enhancer - Mooranian, Armin; Negrulj, Rebecca; Chen-Tan, Nigel; Watts, G.; Arfuso, Frank; Al-Salami, Hani (Dove Medical Press Ltd., 2014)
The authors have previously designed, developed, and characterized a novel microencapsulated formulation as a platform for the targeted delivery of therapeutics in an animal model of type 2 diabetes, using the drug probucol (PB). The aim of this study was to optimize PB microcapsules by incorporating the bile acid deoxycholic acid (DCA), which has good permeation-enhancing properties, and to examine its effect on microcapsules’ morphology, rheology, structural and surface characteristics, and excipients’ chemical and thermal compatibilities. Microencapsulation was carried out using a BÜCHI-based microencapsulating system established in the authors’ laboratory. Using the polymer sodium alginate (SA), two microencapsulated formulations were prepared: PB-SA (control) and PB-DCA-SA (test) at a constant ratio (1:30 and 1:3:30, respectively). Complete characterization of the microcapsules was carried out. The incorporation of DCA resulted in better structural and surface characteristics, uniform morphology, and stable chemical and thermal profiles, while size and rheological parameters remained similar to control. In addition, PB-DCA-SA microcapsules showed good excipients’ compatibilities, which were supported by data from differential scanning calorimetry, Fourier transform infrared spectroscopy, scanning electron microscopy, and energy dispersive X-ray studies, suggesting microcapsule stability. Hence, PB-DCA-SA microcapsules have good rheological and compatibility characteristics and may be suitable for the oral delivery of PB in type 2 diabetes.